Psychosocial and clinical characteristics in Takotsubo syndrome - Okezi Obrutu; Yujie Cui; Jenna Maughan; Paul Marano; Janet Wei; Martha Gulati; Marie Lauzon; Romana Herscovici; Chrisandra Shufelt; Natalie Rojas; Benita Tjoe; Thomas Rutledge; et al. (Biology of Sex Differences)
Abstract Background Takotsubo Syndrome (TTS) is an acute form of heart failure that disproportionately impacts post-menopausal women. The brain-heart connection is considered a pathway for TTS pathophysiology leading to investigations of the role of psychological, psychosocial, and personality factors in TTS. Objectives We compare psychosocial characteristics among a subset of individuals with confirmed TTS and those who had symptoms adjudicated as non-TTS in our online Takotsubo registry (n = 104). We also evaluate differences in TTS clinical characteristics among those with and without symptoms of PTSD and depression. Methods The Smidt Heart Institute Takotsubo registry enrolls individuals with a history of TTS sourced through physician referrals, medical records review, peer- and self-referrals. Psychosocial characteristics were assessed using questionnaires validated in acute coronary syndrome populations. Hedge’s g effect sizes were computed to compare differences in perceived stress, depression symptoms, and post-traumatic stress disorder (PTSD) symptoms relative to TTS status. Results Compared to participants confirmed to be non-TTS, those with adjudication-confirmed TTS had worse mean psychosocial scores (indicative of worse psychosocial characteristics). After adjusting for age at event, BMI, race, and smoking status, the Hedge’s g effect size for depressive symptoms was moderate [0.60 (-0.03, 1.22)] while effect sizes for other psychosocial measures were minimal (Trait anxiety: [0.01 (-0.58, 0.60)], PTSD symptoms [0.13 (-0.46, 0.73)], perceived stress [0.06 (-0.53, 0.65)]. Effect sizes were relatively lower following adjustment, largely driven by participants’ age at first event. Individuals with elevated PTSD symptoms were significantly younger at their first TTS event compared to those with minimal or no symptoms (54 ± 8 vs. 61 ± 10; p = 0.005). QTc was relatively longer among individuals with elevated PTSD symptoms (483 ± 40 msec vs. 465 ± 32 msec; p = 0.08) and elevated depressive symptoms (481 ± 33 msec vs. 464 ± 36 msec; p = 0.07), although the differences were not statistically significant. Conclusions Psychosocial characteristics including PTSD, depression, and stress are common among women with TTS, and age at the time of TTS event is a potentially important moderator of this relationship. We did not find Trait-anxiety or early childhood trauma to be associated with TTS in our cohort.